2011
DOI: 10.1111/j.1601-6343.2011.01527.x
|View full text |Cite
|
Sign up to set email alerts
|

Transversal maxillary dento‐alveolar changes in patients treated with active and passive self‐ligating brackets: a randomized clinical trial using CBCT‐scans and digital models

Abstract: The anticipated translation and buccal bone modeling using active or passive SLBs could not be confirmed. Because of the large interindividual variation, a patient-specific analysis seems to be mandatory as individual factors like pre-treatment teeth inclination and occlusion influenced the treatment outcome of the individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
77
3
36

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 31 publications
8
77
3
36
Order By: Relevance
“…In accordance with our findings, they stated that both groups showed buccal tipping of molars. Cattaneo et al 12 indicated that transversal expansion of the upper arch was achieved by buccal tipping in a Damon group, which is in parallel with our results.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In accordance with our findings, they stated that both groups showed buccal tipping of molars. Cattaneo et al 12 indicated that transversal expansion of the upper arch was achieved by buccal tipping in a Damon group, which is in parallel with our results.…”
Section: Discussionsupporting
confidence: 82%
“…12 Another may be the different torque values on the maxillary molar brackets. The low buccal root torque and increased tipping of the maxillary molars in the Damon group would increase the risk of future relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also found a greater increase in the mandibular intermolar width for the self-ligation group, although there were no differences in the intercanine width [Jiang and Fu, 2008;Pandis et al, 2010]. Two of these studies, however, used differing archwire sequences and archforms similar to our study [Jiang and Fu, 2008;Pandis et al, 2010] and Fleming et al self-ligating brackets and similar low friction systems, which leads us to believe that physiologic buccal expansion and alveolar bone generation is questionable [Franchi et al, 2006;Cattaneo et al, 2011].…”
Section: Discussionmentioning
confidence: 44%
“…Similar forces applied at the bracket produce substantially more (9u-14u) tipping. 2,10,16 Most importantly, lateral tooth movements caused buccal cortical bone to form. Since the bone was initially 1.4 mm thick, and the teeth were moved 0.96 mm, final thickness should have been 0.44 mm.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Tipping produces compressive forces concentrated in the cervical and apical thirds of the tooth's root. 4 Strains that exceed 3000 me are considered problematic, producing microcracks that accumulate and eventually lead to failure.…”
Section: Introductionmentioning
confidence: 99%